SOCIAL AND LEGAL ASPECTS OF LEGISLATIVE REGULATION OF THE CONCEPT OF MOTHERHOOD IN KYRGYZSTAN - Kubanychovna, Alimbekova Zhyldyz; Manasovna, Tursunbaeva Cholpon; Kubanychbekovna, Sulaymanova Baktygul (Veredas do Direito, 2026)
Legislative regulation of social relations is the most complex task of the lawmaking process. In most cases, legislators encounter interpretations of terminological and definitional categories of certain phenomena in social relations. Motherhood is one of these. The ambiguity of this conceptual category requires a search for the intrinsic form of defining motherhood. This study summarized the most meaningful aspects of the concept of motherhood in philosophical, sociological, and legal understandings and developed the most significant features for legislatively enshrining the concept of motherhood. It is necessary to consider it within the system of family, fatherhood, and childhood.